(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In the past few years, there has been an increase in the demand for polymer blends to obtain the desired properties that it could not obtain from individual polymer. And to obtain surface or local polymer blends and in a specific place on the surface of the matrix for the purpose of improving the different characteristics required and according to the specific use, an attempt was made to manufacture binary polymers blends [(HDPE:PVC), (HDPE:PP) and (HDPE:SAN)] by using the friction stir processing (FSP) method on the surface of the matrix ( HDPE ) at depth 3 mm from the surface and with different percentages (10, 15, 20 and 25 %) for each of (PVC),(SAN), (PP) polymeric materials added to the matrix (HDPE). From the mechanical tests which included bending and impact tests it was obtained values indicating a marked increase in mechanical properties at percentages (85% and 34%) from the results achieved for the polymer blends (85%HDPE: 15%PP) and (85% HDPE: 15 % PVC) Respectively. Based on the results obtained, and this demonstrate the success of the FSP method to preparation of different polymer blends and most of these polymers have high efficiency and without have any internal or external defects.